Tumor-Associated Microbiota in Proximal and Distal Colorectal Cancer and Their Relationships With Clinical Outcomes - Jin, Min; Shang, Fumei; Wu, Jingjing; Fan, Qilin; Chen, Chen; Fan, Jun; Liu, Li; Nie, Xiu; Zhang, Tao; Cai, Kailin; Ogino, Shuji; Liu, Hongli (Frontiers in Microbiology, 2021)
The proximal and distal sub-sites of colorectal cancer (CRC) have distinct differences in their embryonic origin, epidemiology, and prognosis. Therefore, they are not considered as the same disease. However, the possible difference in microbial characterization of the two sub-sites of CRCs is still unclear. In this study we explored tumor microbiota diversity and composition difference in patients with proximal (N=187) and distal CRC (N=142). This was carried out on cancer tissues and adjacent tissues using bacterial 16S rRNA sequencing. Kaplan-Meier method was used to analyze the correlation between differential flora and overall survival rate of the patients. It was found that there were significant differences in tumor microbial characteristics between proximal and distal CRC tissues. The microbiota communities were distinctly richer in proximal colon tumor tissues than in the distal CRC tissues. Microbial diversity and structure was relatively constant in the paracancerous normal tissues of the proximal and distal colorectum. Generally, microbial communities of CRC tumor tissues were composed of Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. Alpha diversity in proximal and distal CRC tumor tissues was closely related to specific microflora. The abundance of Fusobacteria was associated with age of patient, tumor diameter, and tumor microsatellite instability (MSI) status of the patients. Moreover, Fusobacteria enrichment was associated with poor prognosis especially in patients with proximal colon cancers, but not in patients with distal CRC. In conclusion, proximal and distal subsites of the CRC present distinct microbiota diversity and community structures. The differences indicates that there are different risk factors across anatomical subsites of CRC, which may provide new strategy for precise prevention and treatment of CRC in the future.